2-Chlorofatty Aldehyde Elicits Endothelial Cell Activation - McHowat, Jane; Shakya, Shubha; Ford, David A. (Frontiers in Physiology, 2020)
Endothelial dysfunction is a hallmark of inflammation. Neutrophil interactions with the vascular endothelium have significant effects on vascular wall biology and pathophysiology. Myeloperoxidase (MPO)-derived oxidant products released from neutrophils may serve as mediators of inflammation and endothelial dysfunction. 2-Chlorofatty aldehyde (2-ClFALD) is the direct oxidation product of MPO-derived hypochlorous acid (HOCl) targeting plasmalogen phospholipids. The role of 2-ClFALD in endothelial dysfunction is poorly understood and may be dependent on the vascular bed. This study compared the role of 2-ClFALD in eliciting endothelial dysfunction in human coronary artery endothelial cells (HCAEC), human lung microvascular endothelial cells (HLMVEC) and human kidney endothelial cells (HKEC). Profound increases in selectin surface expression as well as ICAM-1 and VCAM-1 surface expression were observed in HCAEC and HLMVEC. The surface expression of these adherence molecules resulted in robust adherence of neutrophils and platelets to 2-ClFALD treated endothelial cells. In contrast to HCAEC and HLMVEC, 2-ClFALD-treated HKEC had substantially reduced adherence molecule surface expression with no resulting increase in platelet adherence. 2-ClFALD-treated HKEC did have an increase in neutrophil adherence. All three endothelial cell lines treated with 2-ClFALD displayed a time-dependent loss of barrier function. Further studies revealed the subcellular localization of 2-ClFALD using a synthetic alkyne analog of 2-ClFALD in human coronary artery endothelial cells and in human lung microvascular endothelial cells. Click chemistry experiments revealed 2-ClHDyA localizes to ER and Golgi. These findings indicate 2-chlorofatty aldehydes promote endothelial cell dysfunction with disparate degrees of responsiveness depending on the vascular bed of origin.